A Study On The Increasing Demand For Outbound Leisure Travel To European Countries Among Residents Of Hyderabad, India (PUSA Journal of Hospitality and Applied Sciences, 2020)
Background: “Tourism is the temporary, short-term movement of people to destinations  outside the places where they normally live and work and their activities during the stay at  each destination.” Today tourism is a global phenomenon, with people willing to travel the  entire length and breadth of this globe for leisure. Travelling off late has become a hobby for  many, people are travelling round the globe to explore places and some of them have even  made travelling an ultimate goal in their life’s. With growing awareness about destinations,  added with disposable income a lot of Hyderabadi’s off late have started travelling to Europe  to fulfil their wanderlust. Objective: To explore the various reasons for the increasing  demand for outbound leisure travel to European countries among residents of Hyderabad.  Methodology: In this study, a quantitative research method was used and research data was  collected through an interview with a leading travel agency in Hyderabad, India. It is an  explorative research and a questionnaire was used for this research based on which the travel  agent was able to give us data from the database of bookings done to Europe in the last 2  years. Results: The major reason for people travelling to Europe was for their Honeymoon,  for which they have been saving up, for some of them it’s a once in a lifetime opportunity  to travel to Europe. The second category of travellers was the wealthy lot, who would travel  along with their families. There is another category, the Solo traveller, who saves for an entire  year to travel to one European country. A minuscule percentage of people do travel to Europe  with their friends and some of them travel to Europe for adventure as well. Conclusion: With  the ever-growing social media awareness, disposable income, budget airlines, hotels deals  added with a completely customisable travel plans a lot of residents from Hyderabad are  spending their holidays in Europe.
Keywords: Tourism; Leisure; wanderlust; Disposable Income; Solo Traveller